2020
DOI: 10.1103/physrevresearch.2.033452
|View full text |Cite
|
Sign up to set email alerts
|

Functional sensitivity and mutational robustness of proteins

Abstract: Sensitivity and robustness appear to be contrasting concepts. However, natural proteins are robust enough to tolerate random mutations, meanwhile be susceptible enough to sense environmental signals, exhibiting both high functional sensitivity (i.e., plasticity) and mutational robustness. Uncovering how these two aspects are compatible is a fundamental question in the protein dynamics and genotype-phenotype relation. In this work, a general framework is established to analyze the dynamics of protein systems un… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…To quantify such a scale-free property, it is necessary to introduce the power laws to describe the vibrations of the proteins. Previous studies have shown that the vibrational spectrum of proteins obeys a power-law distribution (Reuveni et al 2008), and the rank-size distribution of the inverse of eigenvalues follows a Zipf-like distribution (Tang et al 2020; Tang and Kaneko 2021; Xie et al 2022). In SI Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To quantify such a scale-free property, it is necessary to introduce the power laws to describe the vibrations of the proteins. Previous studies have shown that the vibrational spectrum of proteins obeys a power-law distribution (Reuveni et al 2008), and the rank-size distribution of the inverse of eigenvalues follows a Zipf-like distribution (Tang et al 2020; Tang and Kaneko 2021; Xie et al 2022). In SI Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S2). Moreover, our study focuses primarily on the global dynamics (e.g., slowest modes) that are robust to the local variations in native structures (Bahar et al 2010; Tang et al 2020). Such insensitivity to prediction confidence can further strengthen our conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…These remarkable population-spanning correlations were replicated for a network model of the brain with experimentally based interareal connectivity when the network dynamics was tuned to criticality (Haimovici et al, 2013). Since then, they have also been observed for bacterial colonies (Chen et al, 2012), insect swarms (Attanasi et al, 2014b), and globular proteins (Tang et al, 2017(Tang et al, , 2020. Here, we explore specifically the analogy in scale-free correlations between animal groups and brain dynamics at the scale of local population activity during motor outputs in nonhuman primates and down to the cellular scale of single neuron interactions during sensory processing in mice.…”
Section: Introductionmentioning
confidence: 70%
“…To quantify such a scale-free property, it is necessary to introduce the power laws to describe the vibrations of the proteins. Previous studies have shown that the vibrational spectrum of proteins obeys a power-law distribution ( Reuveni et al 2008 ), and the rank-size distribution of the inverse of eigenvalues follows a Zipf-like distribution ( Tang et al 2020 ; Tang and Kaneko 2021 ; Xie et al 2022 ). In supplementary figure S6, Supplementary Material online, several proteins are provided as examples.…”
Section: Resultsmentioning
confidence: 99%